2014
DOI: 10.1111/jog.12297
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of estrogen in the prevention of intrauterine adhesions after hysteroscopic septal resection: A prospective, randomized study

Abstract: Estrogen treatment was not found to prevent intrauterine adhesions or improve reproductive outcome after hysteroscopic septal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 11 publications
1
25
1
Order By: Relevance
“…We identified 8 studies evaluating the role of hormonal therapy in preventing IUA [22,23,26,27,30,31,38,39]. Seven studies [22,23,26,27,30,31,38] have already been analyzed in the other ''Results'' sub-sessions.…”
Section: Post-operative Hormonal Therapymentioning
confidence: 98%
“…We identified 8 studies evaluating the role of hormonal therapy in preventing IUA [22,23,26,27,30,31,38,39]. Seven studies [22,23,26,27,30,31,38] have already been analyzed in the other ''Results'' sub-sessions.…”
Section: Post-operative Hormonal Therapymentioning
confidence: 98%
“…114 Estrogen therapy alone has not been found to consistently prevent intrauterine adhesion formation or to improve reproductive outcomes; in a number of studies better fertility outcomes were associated with use of estrogen in combination with other prophylactic methods. 115,116 A systematic review of 5 trials concluded that the use of an antiadhesion barrier gel is associated with a decreased incidence of de novo intrauterine adhesions; however, this did not translate to an increase in live birth rate. 117 Another study comparing reproductive outcomes after operative hysteroscopy suggested no difference in the use of absorbable barriers including sodium hyaluronate and carboxymethylcellulose compared with a removable physical barrier (pediatric Foley), however, patients who underwent surgical hysteroscopy without adhesion prophylaxis had a reduced chance of pregnancy.…”
Section: Risk Reductionmentioning
confidence: 99%
“…Estrogen has been widely used in the prevention of IUA following operative hysteroscopy. Roy et al (26) reported that estrogen treatment reduced the incidence rate of IUA from 6.9 to 0%. In the present study, estrogen treatment significantly prevented the IUA-mediated increase in the serum levels of TGF-β1, EGF and PDGF-BB, indicating that estrogen may inhibit the development of IUA.…”
Section: Discussionmentioning
confidence: 99%